Nanotube breakthroughs: unveiling the potential of carbon nanotubes as a dual therapeutic arsenal for Alzheimer’s disease and brain tumors - Elsori, Deena; Rashid, Gowhar; Khan, Nihad Ashraf; Sachdeva, Punya; Jindal, Riya; Kayenat, Falak; Sachdeva, Bhuvi; Kamal, Mohammad Azhar; Babker, Asaad Ma; Fahmy, Sherif Ashraf (Frontiers in Oncology, 2023)
Alzheimer’s disease (AD) and brain tumors are debilitating neurological conditions that pose significant challenges in current medical practices. Existing treatment options for AD primarily focus on symptom management, and brain tumors often require aggressive therapeutic approaches. Novel disease-modifying strategies and therapeutic agents are urgently needed to address the underlying causes of AD pathogenesis and improve brain tumor management. In recent years, nanoparticles (NPs) have shown promise as valuable tools in diagnosing and managing various brain disorders, including AD. Among these, carbon nanotubes (CNTs) have garnered attention for their unique properties and biomedical potential. Their ability to cross the blood-brain barrier (BBB) with ease opens up new possibilities for targeted drug delivery and neuroprotection. This literature review aims to explore the versatile nature of CNTs, which can be functionalized with various biomolecules or substances due to their sp2 hybridization. This adaptability enables them to specifically target cells and deliver medications under specific environmental conditions. Moreover, CNTs possess an exceptional capacity to penetrate cell membranes, making them valuable tools in the treatment of AD and brain tumors. By delving into the role of CNTs in biomedicine, this review sheds light on their potential in managing AD, offering a glimpse of hope for effective disease-modifying options. Understanding the mechanisms of CNTs’ action and their capabilities in targeting and delivering medication to affected cells will pave the way for innovative therapeutic strategies that can improve the lives of those afflicted with these devastating neurological conditions. The exploration of CNTs as a dual therapeutic arsenal for both brain tumors and Alzheimer’s disease holds great promise and may usher in a new era of effective treatment strategies for these challenging conditions.